A case example of Tier 1 PBIS implementation in a high school. Issue 1 (2nd January 2022) - Bruhn, Allison Leigh; Estrapala, Sara; Rila, Ashley; Colbert, Justin
ABSTRACT: In recent years, high schools have turned to PBIS to address issues related to dropout rates, school climate, and disciplinary practices. However, high schools pose unique implementation challenges when compared to elementary and middle schools, such as large school sizes, organization and culture focused on academics rather than behavior, and the developmental level of students. These challenges can impact buy-in, fidelity, and outcomes, as well as long-term sustainability. Thus, the purpose of this case study is to describe one high school's approach to Tier 1 systems, data, and practices; including professional development, roll-out, and implementation procedures. Through a one-year partnership with a local university, the high school demonstrated improvements in fidelity, student outcomes, and buy-in. Limitations and implications for research and practice are discussed.